PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA - Maritua Simatupang (JURNAL GLOBAL EDUKASI, 2019)
Abstract: The purpose of this study was to determine the application of the Problem Solving learning model to improve student learning outcomes in learning Physics of Global Warming Symptoms in class XI of SMA Negeri 1 Pahae Julu in the academic year 2018/2019. This research is a classroom action research, with research subjects of class XI students of SMA Negeri 1 Pahae Julu, totaling 30 people. The object of this research is student learning outcomes through the application of the Problem Solving Method Approach. The instrument used was a multiple choice test consisting of 10 items. The results showed that in the first cycle there were 22 students who completed or 73.33% of the 30 students who took the test. The mastery level of students in the first cycle of 73.67% is in the category of